Macro-propagation of Taxus baccata Linn. : a Novel Method for Conserving a Critically Endangered Medicinal Plant - Aslam, Mohd; Rather, Mohd Sidiq (Indian Forester, 2008)
Himalayan Yew(Taxus baccata Linn.), an important medicinal plant, is critically endangered due to over-exploitation for the isolation of Taxol, an exciting anti-cancer drug from its bark and leaves. Since the species is unisexual and its natural regeneration via seeds is poor and as the seed raised plants add little growth, propagation by stem cuttings was tried and considerable success was achieved after making use of different auxins (IAA, IBA and NAA) in different concentrations. Of the 10 treatments studied, IBA at 500ppm performed best, registering higher callusing percentage, rooting percentage, number of roots and length of roots in the juvenile shoot cuttings of the species. The results achieved through the application of auxins may possibly be the only practical and viable option for augmenting natural regeneration and also for the large scale propagation and thereby conservation of this threatened versatile Himalayan asset. The technique evolved will be most handy and can be applied any where in its natural habitat for overcoming the chances of its extinction.